LEXICOGRAPHY AS A POLITICAL ACT: A general discussion - Keburia, Mariam (Online Journal of Humanities ETAGTSU, 2021)
This article highlights an interdisciplinary, collaborative and multi-dimensional character of lexicography, its role in a social context, its functions that go beyond describing and documenting a language. Particular attention is given to the capacity of lexicographers to consider not only a language domain or linguistic qualifications of word entries, but also to reflect values, social and political trends of the particular speech community. The article claims that compiling a dictionary (especially in modern times) can be a distinctly political act. Lexicographers of our times (well equipped with ICT tools, means of quick access to knowledge and data) select the frequently used, trendy words or phrases that usually go viral. By knowing and acknowledging dictionary users’ needs, lexicographers make impact. The article makes one of the well-established dictionary publishing brands into loop - Merriam Webster that stood out and responded against the US politician Donald Trump through its blogs, posts, trending words and even not including definitions of Trump’s vocabulary in the dictionary. Full Text (PDF)